Doing business in 2006: Creating Jobs - The world bank (Washington (State) : The Worl bank, 2006)
Trata de una serie de informes anuales que investigan las regulaciones que fomentan la actividad empresarial y aquellas que la restringen.
1. Starting a business 2. Dealing with licenses
incluye índice
Col. Admon
Keywords: 1. GETTING CREDIT 2. CLOSING A BUSINESS